Modulation of muscle protein metabolism through amino acid supplementation and exercise in older women - Bukhari, Syed Shabbar Ijaz (2020)
Background: Skeletal muscle plays an important role in our body, not just in terms of locomotion but also for metabolic purposes. It itself is dependent on two main factors: an adequate diet of essential amino acids as well as regular exercise to keep it in functioning condition. As humans age, the ability of the skeletal muscle to function adequately declines, largely due to age-related muscle loss. This muscle loss has been studied in great detail mostly in men aged 60 and above. It is also well-known that leucine is the main driver of anabolic response to protein supplementation.